Kreasi Minuman Es Soda Gembira Siwalan untuk Memperdaya UMKM Desa untuk Meningktkan Taraf Perekonomian Masyarakat Desa : Studi Kasus di Desa Pragaan Daya - Salsabila Rohadi; Afrian Wahyu Dewa Nuswantara; Muffarijul Ikhwan; Ida Wahyuliani (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2024)
Pragaan Daya Village is a village located in Pragaan District, Sumenep Regency, East Java Province. Pragaan Daya Village is a village that has a thousand abundant resources, both natural resources and human resources. This wealth of resources should be used as best as possible to support the economy of the community. As is known, in this village there are abundant siwalan fruit plants which are known to have a different taste from siwalan fruits in other places. The siwalan fruit in this village has a legit and high-quality taste that makes this siwalan fruit a pity if it is not processed properly. So by doing so, we, the KKNT students of Trunojoyo Madura University, help create this siwalan fruit so that later it can become an MSME idea for the community in Pragaan Daya village. So that the creation of this siwalan fruit can be known to the wider community and can become an economic field for the community.